Oguchi's Disease With Mizuo-Nakamura Phenomenon - Sugandha Goel; Debmalya Das; Saurabh Kumar; Rupak Roy; Sudipta Das; Eesh Nigam (Delhi Journal of Ophthalmology)
Oguchi's disease is an unusual form of congenital stationary night blindness with autosomal recessive inheritance. Mizuo-Nakamura phenomenon is classical of Oguchi's disease. Full-field electroretinogram shows absent rod response and essentially normal cone-mediated response. The mixed rod–cone response has a negative configuration with relatively well-preserved oscillatory potentials. It recovers to a near normal level after a long period of dark adaptation. We herein report a case of Oguchi's disease with Mizuo-Nakamura phenomenon.